The Use of Read, Cover, Remember, Retell (Rcrr) Strategy in Improving Students’ Reading Comprehension Ability - Marpaung, Marlin Steffi; Sinaga, Risnawaty (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2019)
Reading is one of the important skills in English needed by the second language learner. The purpose of this study is to find out is there a significant difference on students’ reading comprehension through Read, Cover, Remember and Retell (RCRR) strategy. The population were VII grade students of SMPN 10 Cimahi. They were divided into two groups, the experimental and conventional group. The experimental group was taught using RCRR strategy while the conventional group was taught using conventional method. This study used quantitative research method and experimental design by using pre-test and post-test. The study was designed to find out the answer of the following questions: Are the students have same level of ability before the treatment? Is there a significant difference on students’ achievement in reading comprehension between the experimental and conventional group? What is the students’ response toward Read, Cover, Remember and Retell (RCRR) strategy?. The instrument used for this study is reading comprehension test and a questionnaire. The result of this study showed that there was a significant difference on students’ achievement in reading comprehension with mean score of pre-test was 40.27 and mean score of post-test was 73.47. The result of the questionnaire toward the students’ responses was 68% positive. It indicated that students had a positive response toward the RCRR strategy. Furthermore, the suggestion for the English teachers, it is recommended to use RCRR strategy to teach reading comprehension in their classes because it can improve the students’ reading comprehension ability.